Nyaya panchayats as instruments of justice - Mathur, S. N.; Institute of Social Sciences (New Delhi, India) (New Delhi : Published for Institute of Social Science by Concept Pub., 1997)
With reference to India
Includes bibliographical references and index
Keywords: Neighborhood justice centers -- India; Panchayat -- India